A non-coding RNA controls transcription of a gene encoding a DNA binding protein that modulates biofilm development in Bartonella henselae. (October 2020) - Okaro, Udoka; George, Sierra; Valdes, Sabrina; Macaluso, Kevin; Anderson, Burt
Abstract: Bartonella henselae ( Bh ) is a Gram-negative zoonotic bacterium that can grow as large aggregates and form biofilms in vitro dependent upon the adhesin BadA. Previously, we reported that the Houston-1 strain of Bh has a family of nine small, highly-expressed intergenic transcripts called B artonella r egulatory t ranscripts, Brt1-9 . Each of the Brts bears a stem and loop structure on the 3′ end followed by a gene encoding a DNA binding protein called the T ranscriptional r egulatory p roteins, Trp1-9 . RNA-seq analysis of laboratory-grown bacteria revealed the trps were poorly transcribed suggesting that the 3′ stem and loop on the Brts results in transcript termination upstream of the trp genes under these conditions. Here we demonstrate that transcription of brt1 continues into trp1 when Bh is grown in a biofilm. Deletion of brt1, or just the 3′ terminus of brt1 (containing the stem and loop structure), resulted in increased transcription of both trp1 and badA and increased biofilm formation. Trp1 was shown to directly bind the putative badA promoter region as demonstrated by an electrophoretic mobility shift assay (EMSA). Our data suggest that the 3′ end of brt1 responds to a stimulus generated by growth of Bh in an in vitro biofilm to allow increased trp1 transcription. We further show that transcription of trp1 increases under conditions consistent with the mammalian host but is not highly expressed in the cat flea vector until the bacterium is excreted into the flea feces. Based on these data, we hypothesize that the 3' end of Brt1 functions to control trp1 transcription and Trp1 in turn results in increased badA expression and enhanced biofilm formation.